2015
DOI: 10.1002/chem.201406409
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine in a Single Stranded Region of Anticodon Stem–Loop tRNA Models is Prone to Oxidatively Generated Damage Resulting in Dehydroguanidinohydantoin and Spiroiminodihydantoin Lesions

Abstract: Oxidation of RNA hairpin models corresponding to anticodon stem-loop (ASL) of transfer RNA led to RNA damage consisting solely of a unique loop guanine oxidation. Manganese porphyrin/oxone treatment of RNA resulted in dehydroguanidinohydantoin (DGh; major) and/or spiroiminodihydantoin (Sp) lesions. Ribose damage was not observed. This two-electron transfer oxidation reaction allowed the identification of guanine oxidation products for further study of RNA species carrying a unique lesion at a single G to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In contrast, the use of cyt c /H 2 O 2 resulted in a significant decrease in the S2U content and an increased amount of H2U. For the reactions performed for 1 and 3 h, the ratio of the canonical nucleosides remained virtually constant, which confirmed that the guanine residues in an RNA chain were not oxidized under the conditions applied …”
Section: Resultsmentioning
confidence: 80%
“…In contrast, the use of cyt c /H 2 O 2 resulted in a significant decrease in the S2U content and an increased amount of H2U. For the reactions performed for 1 and 3 h, the ratio of the canonical nucleosides remained virtually constant, which confirmed that the guanine residues in an RNA chain were not oxidized under the conditions applied …”
Section: Resultsmentioning
confidence: 80%
“…Studies to monitor cellular excretion of OG from DNA or RNA observe up to ~3-fold more OG in RNA than DNA supporting high levels of RNA oxidation in vivo [138]. Reports from our laboratory [139, 140], Pratviel and coworkers [141], and Thorp and coworkers [142] have described RNA oxidation in various contexts. The recent work by Pratviel and coworkers analyzed G oxidation by a manganese porphyrin complex and KHSO 5 in model anticodon tRNA stem-loops to identify the oxidation product Sp [141].…”
Section: Additional Contexts and Reaction Partners Of G Studied Unmentioning
confidence: 95%
“…Reports from our laboratory [139, 140], Pratviel and coworkers [141], and Thorp and coworkers [142] have described RNA oxidation in various contexts. The recent work by Pratviel and coworkers analyzed G oxidation by a manganese porphyrin complex and KHSO 5 in model anticodon tRNA stem-loops to identify the oxidation product Sp [141]. We found 1 O 2 oxidation of G in ssRNA can yield Sp or Gh in a pH-dependent reaction [140], and a nickel macrocycle to activate the oxidant KHSO 5 yields 2Ih [140].…”
Section: Additional Contexts and Reaction Partners Of G Studied Unmentioning
confidence: 99%
“…37, 38 OG has been found in both cellular DNA and RNA, while Gh and Sp have thus far been characterized only in cellular DNA and in RNA oligomers mimicking the tRNA anticodon loop or short single strands of RNA. 18, 39, 40 The latter lesion, Sp, exists as a pair of enantiomers ( R -Sp and S -Sp) as the free base, which form a pair of diastereomers once attached to the chiral ribose or 2′-deoxyribose components in nucleic acids. 41 …”
Section: Introductionmentioning
confidence: 99%